1999
DOI: 10.1074/jbc.274.49.34590
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of the Apolipoprotein B mRNA-editing Region

Abstract: Apolipoprotein (apo) B mRNA editing is the deamination of C 6666 to uridine, which changes the codon at position 2153 from a genomically encoded glutamine (CAA) to an in-frame stop codon (UAA). The apoB mRNA-editing enzyme complex recognizes the editing region of the apoB pre-mRNA with exquisite precision. Four sequence elements spanning 139 nucleotides (nt) on the apoB mRNA have been identified that specify this precision. In cooperation with the indispensable mooring sequence and spacer element, a 5 efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…3C, lane 6). The results suggest that the double-stranded RNA binding domain is unlikely to play a major role in the complementation function of ACF, despite predictions from folding algorithms that apoB RNA in the region of the edited base adopts a conformation that resembles double-stranded RNA (35)(36)(37). This said, apoB RNA binding activity was reduced with both the ⌬(380 -402) and ⌬(438 -515) mutants (Fig.…”
Section: Deletional Analysis Of Acf: Functional Implications Frommentioning
confidence: 94%
“…3C, lane 6). The results suggest that the double-stranded RNA binding domain is unlikely to play a major role in the complementation function of ACF, despite predictions from folding algorithms that apoB RNA in the region of the edited base adopts a conformation that resembles double-stranded RNA (35)(36)(37). This said, apoB RNA binding activity was reduced with both the ⌬(380 -402) and ⌬(438 -515) mutants (Fig.…”
Section: Deletional Analysis Of Acf: Functional Implications Frommentioning
confidence: 94%
“…The weak cross-linking of ASP may be explained by the presence of KSRP in our fractions. Two recent studies re-examined the secondary RNA structure requirements for efficient editing at C 6666 (60,61). Both studies concluded that C 6666 is located at a junction between a double-stranded and a single-stranded RNA region.…”
Section: Discussionmentioning
confidence: 99%
“…Both studies concluded that C 6666 is located at a junction between a double-stranded and a single-stranded RNA region. This junction was localized either at the loop of a hairpin (60) or at the beginning of a doublestranded stem formed by the mooring sequence (nucleotides 6671-6681) and a 3Ј-efficiency element (nucleotides 6718 -6746) (61). A protein that specifically recognizes this junction between a double-stranded and a single-stranded region would fit these models.…”
Section: Discussionmentioning
confidence: 99%
“…A tripartite RNA sequence motif, consisting of an 11-nucleotide mooring sequence, a spacer, and a regulatory element, is required for site-specific RNA editing (4 -8). Recently, a stem-loop model of secondary structure involving the essential sequence required for editing has been proposed (9,10). These cis-acting elements are required for the assembly of an editing complex, the C/U editosome (5,11), and site-specific editing activity.…”
mentioning
confidence: 99%